Effects of smoking and physical exercise on respiratory function test results in students of university: A cross-sectional study. Issue 32 (August 2019) - Dugral, Esra; Balkanci, Dicle
Abstract : Abstract: We explored the effects of smoking and exercise on pulmonary function (PF) in young adults. This was a 2-year, prospective cross-sectional study on university students. We recorded age, gender, weight, height, pulmonary symptoms, smoking status, and sports habits. Spirometry was used to evaluate lung function; we recorded the forced expiratory volume in 1 second (FEV1), the forced vital capacity (FVC), and the FEV1/FVC ratio. A total of 1014 (552 female, 464 male) subjects were included. Smokers reported significantly more wheezing and sputum production than nonsmokers, but exhibited better FVC and FEV1 values. Those who smoked less than half a pack/d had significantly poorer FVC and FEV1 levels than nonsmokers. Smokers exhibited significantly lower FEV1/FVC ratios than nonsmokers. Overall, those who exercised exhibited better FEV1 and FVC levels, but this was attributable entirely to females. The spirometric percentile data were adjusted for gender, age, and height, and used as indicators of health status (good: >90: average: 25–90, poor <25). ln males, PF was associated with regular exercise (good: 7.8, average: 6.5, poor: 14.2, P  = .02). The smoking rate was higher in the "good" group (males: good: 31.3, average: 30, poor: 17.9, P  = .02/females: good: 22.4, average: 17.9, poor: 10.4, P  = .02). On multivariate regression analysis, above-average PF test results were associated with age (1.32 [1.04–1.69]) and exercising at least once per week (4.06 [1.16–14.20]) in males. In females, above-average results were associated with irregular exercise (2.88 [1.36–6.09]), age (1.85 [1.44–2.37]), and exercising until palpitations developed (0.18 [0.04–0.88]). Smoking improves lung function in young adults; these are "healthy smokers." Physical activity did not improve lung function, but the absence of physical activity significantly worsened lung function.